Poststroke Cognitive Impairment: A Longitudinal Follow-Up and Pre/Poststroke Mini-Mental State Examination Comparison - Hong, Chien-Tai; Lee, Hsun-Hua; Chung, Chen-Chih; Chiu, Wei-Ting; Lee, Ting-Yi; Chen, David Yen-Ting; Huang, Li-Kai; Hu, Chaur-Jong; Chan, Lung (Current Alzheimer research, 2022)
Poststroke cognitive impairment (PSCI) is a prevalent cause of disability in people with stroke. PSCI results from either lesion-dependent loss of cognitive function or augmentation of Alzheimer's pathology due to vascular insufficiency. The lack of prestroke cognitive assessments limits the clear understanding of the impact of PSCI on cognition. The present study aims to make a direct comparison of longitudinal cognitive assessment results to clarify the impact of ischemic stroke on PSCI and assess the cognitive decline in PSCI compared to people with Alzheimer's disease (AD). All study participants had their Mini-Mental State Examination (MMSE) at the chronic poststroke stage (≥6 months after stroke), which was compared with prestroke or acute poststroke (<6 months after stroke) MMSE to investigate the two aspects of PSCI. A group of patients with AD was used to reference the speed of neurodegenerative cognitive deterioration. Repeated measures analysis of variance was used to compare the longitudinal change of MMSE. MMSE score between acute and chronic poststroke revealed a 1.8 ± 6.49 decline per year (n=76), which was not significantly different from the AD patients who underwent cholinesterase inhibitors treatment (-1.11 ± 2.61, p=0.35, n=232). MMSE score between prestroke and chronic poststroke (n=33) revealed a significant decline (-6.52 ± 6.86, p < 0.001). In addition, their cognitive deterioration was significantly associated with sex, age, and stroke over the white matter or basal ganglia. Ischemic stroke substantially affects cognition with an average six-point drop in MMSE. The rate of cognitive decline in PSCI was similar to AD, and those with white matter or basal ganglia infarct were at greater risk of PSCI.